Study on Retail Marketing of Human and Various Factors Affecting It: Exploring the Impact of Various Factors on Retail Marketing (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Retail Marketing defined as “individuals or groups,acquiring, using and disposing of products, services, ideas or experiences”(Arnould, Price & Zinkha, 2004). There are numbers of different theoriesexplaining Retail Marketing (Statt, 1997; Blackwell, Minrard, and Engel, 2006;Chaudhuri, 2006) and a huge amount of literature currently exists (Grunert2002; Botonaki, Ploymeros, Tsakorodou, & Mattas, 2006; Friese, Wanke, andPlessner, 2006). There are different number of characteristics, which canimpact on Retail Marketing (Figure 1), which includes from demographicvariables to purchase and consumption behaviours.